2019
DOI: 10.1371/journal.pone.0215129
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication overrides warming as a stressor for a temperate African seagrass (Zostera capensis)

Abstract: Despite knowledge that seagrass meadows are threatened by multiple global change stressors, significant gaps exist in current knowledge. In particular, little is known about the interactive effects of warming and eutrophication on seagrasses globally, or about responses of African seagrasses to global change, despite these ecosystem engineers providing critical goods and services to local livelihoods. Here, we report on laboratory experiment assessing the main and joint effects of warming and nutrient enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 65 publications
3
27
1
Order By: Relevance
“…Our results are in line with previous studies which did not observe interactive effects of both factors on adult temperate seagrass plants (Touchette and Burkholder, 2002;Kaldy, 2014;Moreno-Marín et al, 2018;Mvungi and Pillay, 2019;Ontoria et al, 2019) and tropical seagrass plants (Viana et al, in prep). In these studies, the combination of effects of nutrient enrichment of the water column and increasing temperature did not show clear effects on seagrass plants.…”
Section: Seedling Response To Increased Nutrientssupporting
confidence: 94%
See 4 more Smart Citations
“…Our results are in line with previous studies which did not observe interactive effects of both factors on adult temperate seagrass plants (Touchette and Burkholder, 2002;Kaldy, 2014;Moreno-Marín et al, 2018;Mvungi and Pillay, 2019;Ontoria et al, 2019) and tropical seagrass plants (Viana et al, in prep). In these studies, the combination of effects of nutrient enrichment of the water column and increasing temperature did not show clear effects on seagrass plants.…”
Section: Seedling Response To Increased Nutrientssupporting
confidence: 94%
“…In these studies, the combination of effects of nutrient enrichment of the water column and increasing temperature did not show clear effects on seagrass plants. In contrast, other previous studies showed that morphological traits, such as leaf length, growth or number of leaves per shoot, were the most variable traits under the influence of both factors (Bintz et al, 2003;Mvungi and Pillay, 2019). Interactive effects on the response in the %N of the leaves were only observed in Z. marina (Moreno-Marín et al, 2018).…”
Section: Seedling Response To Increased Nutrientscontrasting
confidence: 74%
See 3 more Smart Citations